Linguistics : An Interdisciplinary Journal of the Language Sciences (De Gruyter Mouton, 1963)
Linguistics publishes articles and book reviews in the traditional disciplines of linguistics as well as in neighboring disciplines insofar as these are deemed to be of interest to linguists and other students of natural language. The journal also features occasional Special Issues in these fields.